Research on Optimization of Low-carbon Eco-city Indicator System in China from International Comparison Perspective - Shao, Jingmei; Li, Wenhao; Long, Yan; Wei, Fangqiao; Hu, Siyu; Guo, Tingting; Pu, Xiangjun (E3S web of conferences, 2025)
This paper, guided by the goals of “carbon peak” and “carbon neutrality,” examines the Low-carbon Eco-city index systems of developed countries through international comparison. It identifies key points for constructing China’s own index system under these goals and proposes a framework for optimizing China’s Low-carbon Eco-city system. A comparison is made between the China-Singapore Tianjin Eco-city Version 2.0 and Bristol’s urban development index, focusing on the index framework and specific data. The analysis highlights both similarities and differences. By drawing on Bristol’s approach, it suggests increasing the share of renewable energy, developing clean energy, green building materials, renewable energy technologies, and smart technologies, while improving energy efficiency, reducing emissions, and enhancing carbon sink capacity. Based on these findings, relevant strategies for optimizing China’s Low-carbon Eco-city index system are proposed.